Assessment of Chlorogloeopsis as a novel microbial dietary supplement for red tilapia (Oreochromis niloticus) - Steve Skill (Aquaculture, 2010)
A 9week study was conducted to assess the effect of incorporating dietary Chlorogloeopsis on the growth performance, feed utilisation, body composition, haematology and gut microbiota of red tilapia (Oreochromis niloticus). Chlorogloeopsis cells were supplemented to the diet at 0.25%, 0.50% and 1.00%. Compared to the control group, no significant differences of growth parameters or body composition were observed in the Chlorogloeopsis fed fish. However, haematological and gut microbial load appeared to be more sensitive to dietary Chlorogloeopsis. Haematocrit levels increased from 31.0±2.9% in the control group to 32.8±4.2 and 33.3±5.0 in the 0.50% and 1.00% Chlorogloeopsis groups, respectively. The total allochthonous microbial load and lactic acid bacteria levels were elevated but the microbial groups identified and microbial diversity did not differ between the dietary groups. PCR-DGGE fingerprints of the microbial profiles supported this finding but revealed clear differences between the allochthonous and autochthonous communities. Sequence analysis from DGGE fingerprints identified several bacterial clones closely related to bacteria previously isolated from the digestive tract of fish and revealed a Lactobacillus spp. found in all groups was present only as part of the allochthonous communities. Low level dietary applications of Chlorogloeopsis for tilapia aquaculture seem limited but further evaluation is required.